Mixing Profile of Nitrogen and Hydrogen Gases in Monolithic Channel through Computational Fluid Dynamics - MOHAMED RASHIDI, NUR AMIRAH (2021)
Ammonia (NH3) has a very significant value in the fertilizer industry where commonly it was being synthesized via Haber-Bosch process. The process was developed in the early 1900s by Fritz Haber and was later modified to become an industrial process to make fertilizers by Carl Bosch. As the process utilizing high operating conditions, it imposes high capital and extensively an energy-consuming process. Due to the unsustainable process, the researcher initiates an alternative to overcome this drawback by introducing a microfluidic environment with ambient pressure (1 atm) that coherent to the green industry sustainable pathway of growth. This research comprises of simulation method where the three models of monolithic channel were designed via Computational Fluid Dynamics (CFD) approach using ANSYS 19.1 software coupled with FLUENT module. The monolithic channels were constructed in a 50 mm x 10 mm (length x diameter) dimension. The wire elements and wire supports arrangement at different pitch angle were created as the base for nanocatalyst and act as an obstruction in the monolithic channel. This simulation investigated the effect of different configuration in geometry and effect of inputting different temperature towards the dynamic mixing of Hydrogen and Nitrogen gases. Greater mixing will lead to elevation of the NH3 production. Based on the result obtained, the geometry with 45o angle pitch wire supports are perceived to produce the most effective dynamic mixing as it offers great chaotic advection to heighten the mixing as compared to the 90o or 60o pitch tube layout. Different temperature is then investigated to discover the optimum value to create greater mixing. The temperature of 25oC is the best pick because more Ammonia can be produced with a lower temperature looking through from the point of view of endothermic direction.